'I had to bear the brunt'- the impact on worker bodies of the marketisation of aged care. (2nd January 2023) - Martain, Sandra
ABSTRACT: This study reveals the centrality of the exploitation of the worker body in the marketised context of aged care in Australia. Support workers are on the front line of the delivery of aged care services, yet remain low paid, undervalued and subject to increasingly precarious work. They perform a 'Taylorised' labour process within strict task and time requirements, which is at odds with the care needs of aged clients, in both residential facilities and in the private homes of aged clients. A conceptualisation of an 'embodied labour process' of support work is proposed to highlight the depth and complexity of the embodied labour power exploited in this labour process. The study finds that worker bodies experience considerable physical, mental and emotional strain from this exploitation. The study argues that the marketisation of aged care is in fact reliant upon the exploitation of these hidden, vulnerable and disposable worker bodies.